SHARIA BANKING PERFORMANCE IN MAKASSAR - Said, Salmah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This study aims to analyze the performance of Islamic banking in Makassar. Data collected using questionnaires which was distributed to seven Islamic banks. Supporting data obtained from Bank Indonesia, representatives Makassar and Bank Indonesiaâs website. Data then were analyzed using financial ratios, particularly Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR). The results showed that NPF was 1.49% and FDR reached 201.67%. The first ratio indicates low financing problems, while the second shows a high ratio financing provided to society. Furthermore, Islamic principles applied in the system, mechanism, and products offered by the Islamic banking is such a value-added for the societies, which is not found in the conventional ones. The high financial performance of Islamic banking outperforms its counterparts shows significant potential to grow rapidly in the future.Â —–Penelitian ini bertujuan menganalisis kinerja perbankan syariah di Makassar. Teknik pengumpulan data menggunakan kuisioner yang dibagikan kepada tujuh bank syariah. Data pendukung diperoleh dari Bank Indonesia perwakilan Makassar dan website Bank Indonesia. Teknik analisis data menggunakan analisis rasio keuangan, terutama Non Performing Financing (NPF) dan Finanicng to Deposit Ratio (FDR) perbankan syariah secara agregat. Hasil penelitian menunjukkan NPFperbankan syariah di Makassar secara agregat sebesar 1,49% dan FDR sebesar 201,67%. Rasio pertama menunjukkan rendahnya pembiayaan bermasalah, sedangkan rasio kedua menunjukkan tingginya pembiayaan yang diberikan kepada masyarakat. Lebih jauh, penerapan prinsip syariah dalam sistem, mekanisme, dan produk perbankan syariah menjadi nilai tambah bagi masyarakat. Hal ini tidak ditemukan dalam perbankan konvensional. Dengan kinerja keuangan yang kompetitif, maka perbankan syariah memiliki potensi untuk berkembang pesat di masa yang akan datang.Â